Country role models for development success: The case of Costa Rica - Alberto Trejos (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2009)
In this paper, I discuss the reasons for Costa Rica's economic performance over the last quarter of a century. Three complementary sets of policies (investments in human capital, careful stabilization, and an intelligent and aggressive integration into the world economy) explain the successful trends, and can be thought of - at least in hindsight - as a development strategy. While fruitful, this strategy has been incomplete, as there have been less results in other policy areas, including income distribution, infrastructure, adequate taxation and telecoms. These omissions result from the weakness of the political system to deliver decisions and implement chosen policies. Despite these problems, Costa Rica's case is interesting and worthy of study from the perspective of other small, developing countries.
Keywords: O1; O2; O4; O5; 330; economic growth; economic development; economywide country studies; economic planning and policy; Wirtschaftswachstum; Entwicklung; Wirtschaftspolitik; Costa Rica